Electrochemical modification process of anodic alumina membrane - 于美 刘建华 李松梅 (Transactions of Nonferrous Metals Society of China, 2006)
The modification procedure of anodic alumina membrane（AAM） was studied. The AAM structure after modification was characterized by nickel nanowires prepared in AAM. Scanning electron microscopy was used to characterize the topography and structure properties of the AAM and nickel nanowires. The transformation of the current during the voltage reduction was studied. The mechanism of current and structure change during modification was discussed. The results show that a root structure produces aider the AAM modification. The length of the root structure depends on the velocity of the voltage reduction. Slow voltage reduction leads to a large length of the root structure, otherwise, a short length of the root structure. At the end of the modification, the barrier layer is thin enough to be passed by electrons. Hence, the direct electrodeposition of one-dimensional nanowires can be carried out on the AAM with barrier layer and aluminum matrix successfully without any other treatments.